Family caregiver role in care recipient preparedness for hospital discharge: A parallel mediation model. - Nosaiba Rayan-Gharra; Orly Tonkikh; Nurit Gur-Yaish (PLoS ONE, 2025)
Background Family members or friends (caregivers) play a substantial role in supporting health needs of older adults or persons with chronic conditions and accompanying them in acute-care settings. Scarce evidence on the impacts of caregiver engagement in ensuring and explaining medical care during hospitalization calls for further exploration of the role of caregivers along the peri-hospitalization trajectory in supporting hospitalization outcomes. This study aimed to examine the association between pre-admission caregiver support and care recipients' preparedness for discharge and whether caregiver engagement during hospitalization and upon discharge mediates this association. Methods Secondary analysis of a cohort study of 443 internal medicine patients who were accompanied by caregivers. Pre-admission caregiver support, engagement in ensuring and explaining medical care during hospitalization, and covariates like health literacy, demographics and health status were reported by patients during hospitalization. Caregiver involvement in the discharge briefing and care-transition preparedness was reported a week after discharge. Results Multivariate mediation analysis showed significant direct effect (B(unstandardized)=1.55; CI = 0.09-2.99; P = 0.036) of pre-admission caregiver support on care-transition preparedness. The effect was mediated by high caregiver engagement in ensuring and explaining medical care during current hospitalization (Mediated effect (ME)=2.84; CI = 1.78-4.00) and involvement in the discharge briefing (ME = 0.71; CI = 0.20-1.29), controlling for patient and caregiver health and functional status, health literacy, and demographics (Total effect: B(unstandardized)=5.10; CI = 3.21 to 7.01). Of the covariates, only high health literacy levels of the patients (B(unstandardized)=4.56; P < .001) and of the caregivers (B(unstandardized)=6.67; P < .001) were positively associated with preparedness for discharge. Conclusions This study highlights the critical role of caregiver engagement during the hospitalization process as a pathway linking pre-admission support to discharge preparedness. The findings support early identification of caregiving status and health literacy at admission, enabling healthcare providers to tailor communication and better engage caregivers in the discharge process, to ultimately promote smooth care transitions.